Symbiosis - Raath, Jan Philip (Michaelis School of Fine Art, 2024)
This story begins in the late 1700's, a moment at which Western philosophy had decided that: Direct access to reality is impossible. Thinking can only talk about the way the human and the world correlate together. There is a crack in reality. Facts are given to us but their conditions of possibility transcend them.